KUALITAS SPERMATOZOA KAMBING BLIGON DALAM PENGENCER TRIS KUNING TELUR DENGAN PENAMBAHAN BERBAGAI LEVEL EKSTRAK KULIT BUAH NAGA - Maria F. T. Leyn; Henderiana Belli; Wilmientje Marlene Nalley; Petrus Kune; Thomas Mata Hine (Universitas Nusa Cendana, 2021)
The purpose of this study was to examine the effect of adding various concentrations of dragon fruit peel extract (DFPE) in Tris-egg yolk diluent (TEY) on the quality of bligon goat spermatozoa. Semen was collected twice a week using the artificial vaginal method from three year old bligon male goats with normal body conditions and reproductive organs. After the macroscopic and microscopic evaluation, good quality semen with a sperm motility of > 70%, a concentration of > 800 x 106 mL-1, and abnormality of < 15 %, was diluted with TEY + DFPE at a concentration of 0% (P0), 2% (P1), 4% (P2), 6% (P3), 8% (P4), dan 10% (P5). The semen which still had a motility ≥ 70% was then stored at a temperature of 3-5oC. Evaluation of the quality of spermatozoa was carried out every 24 hours until the motility decrease to 40%. The results showed that from day 1 to day 5 of preservation, spermatozoa preserved in TEY + 6% DFPE diluent (P3) had higher motility and viability (P<0,05) than other treatments. The abnormalities of spermatozoa until the 5 day of preservation were below 6%, but showed a significant difference (P<0,05) between treatments that received DFPE suplemention with control (P0). It was concluded that the addition of DFPE in TEY up to 6% could reduce the decrease in sperm quality of bligon goats during in vitro preservation.